Taking a Closer Look at Mental Health Treatment Differences: Effectiveness of Mental Health Treatment by Provider Type in Racial and Ethnic Minorities - Tracey L. Henry; Anuradha Jetty; Stephen Petterson; Helaina Jaffree; Allie Ramsay; Erica Heiman; Andrew Bazemore (SAGE Publishing, 2020)
Objectives: To estimate racial/ethnic differences in the extent to which mental health treatment is obtained from mental health providers, primary care physicians (PCPs), or both and to examine the effects of provider type on change in mental component scores (MCS) of the SF-12 on different race/ethnic groups. Methods: Secondary data analysis of 2008 to 2015 Medical Expenditure Panel Survey (MEPS). Non-institutionalized civilian US population, aged 18 to 64 (N = 62 558). Based on counts of all mental health visits in a calendar year, we identified patients who obtained care from PCPs, mental health provider, PCP and mental health providers and other providers and examined changes in MCS by type of care. Results: 9.9% of Non-Hispanic Whites obtained mental health treatment, compared to 5.0% for Hispanics, 5.3% for Blacks and 5.5% for Other Races ( P  < .001). Non-Hispanic Blacks and non-Hispanic "Other" were more likely than other groups to obtain care from mental health providers only ( P  = .017). All obtaining care solely from PCP had better mental health (mean (se)) MCS: 43.2(0.28)) than those obtaining care solely from mental health provider (39.8 (0.48)), which in turn was higher than for those obtaining care from both PC and MH providers (38.5 (0.31), ( P  < .001). Conclusion: Even when diagnosed with a mental health disorder, Hispanics and Blacks were less likely to seek mental health treatment than Whites, highlighting the continuing disparity. Future research should focus on understanding how and what aspects of integrated care models and other mental health delivery models that reduce disparities and provide greater accessibility.